Efficiency, Safety, and Efficacy of High-Power Short-Duration Radiofrequency Ablation in Patients with Atrial Fibrillation - Xuerong Sun; Jiang Lu; Jinxuan Lin; Tianjie Feng; Ni Suo; Lihui Zheng; Zhimin Liu; Gang Chen; Xiaohan Fan; Shu Zhang; Guodong Niu (Cardiology Research and Practice)
Pulmonary vein isolation (PVI) is the cornerstone therapy of atrial fibrillation (AF). Radiofrequency catheter ablation (RFCA) is performed using a point-by-point method to achieve durable PVI. However, this procedure remains complex and time-consuming, and the long-term clinical outcomes are still not satisfactory. Recently, there has been increasing interest in the clinical application of high-power short-duration (HPSD) approaches in the field of RFCA. HPSD ablation, distinguishing it from the conventional ablation strategy, delivers RF energy at a high power and saves the dwell time at each site. It is unknown whether the HPSD approach can bring some gratifying changes in the field of RF energy ablation. A number of experimental studies and clinical studies have been conducted regarding this topic. The review aimed to summarize the research findings and evaluate the procedural efficiency, safety, and clinical outcomes of the HPSD approach based on the evidence available to date.